Contextualizing Fiqh al-Siyāsah in Indonesia: A Proposed Typology of Islamic Populism - Ulum, Bahrul; Arifullah, Mohd (AHKAM : Jurnal Ilmu Syariah, 2024)
Amid a political atmosphere increasingly polarized by various forms of populism, this article identifies the typology of Islamic populism in Indonesia from the perspective of Islamic political law. It reveals a new horizon by showing the adaptability of fiqh al-siyāsah to the variants of Islamic populism typology. Drawing from different approaches to Islamic populism studies in Indonesia, the article classifies three typologies of Islamic populism in Indonesia: economic-political populism, political Islamism, and political pragmatism. Each has different characteristics and missions of struggle in the political and social context. This article argues that fiqh al-siyāsah functions not only as a tool of legitimacy but also as an adaptive framework that responds to contemporary political dynamics. This adaptability not only refers to the contextualization of sharia principles but also involves adaptations that shape and give birth to more inclusive and beneficial political policies and practices within the framework of Islamic populism in Indonesia. This article expands the horizon of how the integration of political principles of Islamic law in populist movements can influence the dynamics and political policies in IndonesiaAbstrakDi tengah suasana politik yang makin terpolarisasi oleh berbagai bentuk populisme, artikel ini mengidentifikasi tipologi populisme Islam di Indonesia dari perspektif hukum politik Islam. Artikel ini mengungkap cakrawala baru dengan menunjukkan adaptabilitas fiqh al-siyāsah terhadap varian tipologi populisme Islam. Mengacu pada beberapa pendekatan studi populisme Islam di Indonesia, artikel ini mengklasifikasikan tiga tipologi populisme Islam di Indonesia: populisme ekonomi-politik, Islamisme politik, dan pragmatisme politik. Masing-masing memiliki karakteristik dan misi perjuangan yang berbeda dalam konteks politik dan sosial. Artikel ini berargumen bahwa fiqh al-siyāsah berfungsi tidak hanya sebagai alat legitimasi tetapi juga sebagai kerangka adaptif yang merespons dinamika politik kontemporer. Adaptabilitas ini tidak hanya mengacu pada kontekstualisasi prinsip-prinsip syariah tetapi juga melibatkan adaptasi yang membentuk dan melahirkan kebijakan dan praktik politik yang lebih inklusif dan bermanfaat dalam kerangka populisme Islam di Indonesia. Artikel ini memperluas cakrawala tentang bagaimana integrasi prinsip-prinsip politik hukum Islam dalam gerakan populis dapat memengaruhi dinamika dan kebijakan politik di Indonesia.